Représentations et pratiques autour de la ressource en eau des producteurs maraîchers des Andes vénézuéliennes - David Leroy; Alexandra Angéliaume-Descamps; Jean Marc Antoine; Frédérique Blot; Éric Maire; Anne Peltier (VertigO)
This study aims to analyze social representations for water resource of market gardening producers of the high valleys of Venezuelan Andes, whereas this resource constitutes an essential tool of agricultural production. It proposes more particularly to understand how farmers perceive and assess the current state of the resource and identify the justification of their behaviour and agricultural practices. In the 1960s, the introduction of irrigated gardening in the Venezuelan Andes, has profoundly changed the relationship to water for rural societies who have developed particularly efficient systems of appropriation and distribution of the resource particularly effective, both technically and socially. But, nowadays, the farmers perceive fluctuations in the resource that they can interpret as a consequence of climate change, and/or as a result of actual agricultural dynamics. Faced with this phenomena, new practices such as irrigation by micro-irrigation or the preservation of water sources in altitude begin to emerge.